2007
DOI: 10.1021/jp0660987
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Protein Domains and Lipid Bilayer Vesicle Shape Transformations

Abstract: Cellular membranes can take on a variety of shapes to assist biological processes including endocytosis. Membrane-associated protein domains provide a possible mechanism for determining membrane curvature. We study the effect of tethered streptavidin protein crystals on the curvature of giant unilamellar vesicles (GUVs) using confocal, fluorescence, and differential interference contrast microscopy. Above a critical protein concentration, streptavidin domains align and percolate as they form, deforming GUVs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
14
1
Order By: Relevance
“…Similar planar deformations on model membranes have been documented for the flat PinkBAR domain, [6c] the F-BAR protein Nervous Wreck, [21] the autophagosomal coat complex, [18a] and two-dimensional streptavidin crystals. [22] There,t he scaffolding subunits were capable of building large lattices on lipid bilayers,a nalogous to what we report for am ixture of constructs Aa nd B. A distinct property of the vesicles that were deformed by the oligomerizing constructs Aa nd Bi st hat they were much more resistant to spontaneous collapse at the bottom of the observation chamber as most of them survive for 3-5 days instead of collapsing after one day as observed for GUVs with the non-interacting DNAo rigami constructs.F urthermore, the form of the membrane deformations observed here can be correlated with the shape of the individual DNAo rigami subunits,a sd escribed for PinkBAR domains.…”
Section: Methodsmentioning
confidence: 99%
“…Similar planar deformations on model membranes have been documented for the flat PinkBAR domain, [6c] the F-BAR protein Nervous Wreck, [21] the autophagosomal coat complex, [18a] and two-dimensional streptavidin crystals. [22] There,t he scaffolding subunits were capable of building large lattices on lipid bilayers,a nalogous to what we report for am ixture of constructs Aa nd B. A distinct property of the vesicles that were deformed by the oligomerizing constructs Aa nd Bi st hat they were much more resistant to spontaneous collapse at the bottom of the observation chamber as most of them survive for 3-5 days instead of collapsing after one day as observed for GUVs with the non-interacting DNAo rigami constructs.F urthermore, the form of the membrane deformations observed here can be correlated with the shape of the individual DNAo rigami subunits,a sd escribed for PinkBAR domains.…”
Section: Methodsmentioning
confidence: 99%
“…On SLBs, SAv and any target molecule anchored to it can rotate and diffuse laterally (as illustrated by the black arrows in Fig. 1B), provided that the SAv surface density is low enough to prevent two-dimensional protein crystallization [37,38] (the latter was reported to occur at surface densities above 75% relative to that of the crystalline phase, i.e. above 200 ng/cm 2 , on lipid monolayers [39]).…”
Section: Design Of Well-defined Biomimetic Surfacesmentioning
confidence: 99%
“…Streptavidin-membrane interaction has been known to facilitate the aggregation of vesicles for use as potential drug delivery vehicles 18 and has been observed to cause giant vesicles to deform to oblate structures from protein crystallization, 19 however, nanotube formation has not been previously reported. The process is specific to the streptavidin-biotin recognition as vesicles lacking DOPEbiotin were unaffected by streptavidin presence.…”
Section: Resultsmentioning
confidence: 99%
“…The Gast lab has shown that streptavidin crystallized against biotionylated giant vesicles of 1-stearoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (SOPC) produces vesicle ruffling and oblate structure formation. 19,21 As solution pH increased from 4.3 to 6.3, streptavidin crystals grew as long and thin structures with parallel orientation over the membrane surface inducing elongation of the vesicles. Since the isoelectric point of the protein occurs at pH 5-6, it was argued that increasing pH resulted in smaller crystals due to electrostatic repulsive forces.…”
Section: Resultsmentioning
confidence: 99%